Analisis Pengaruh Independensi, Profesionalisme dan Tekanan Anggaran Waktu Terhadap Kualitas Pemeriksaan Atas Laporan Keuangan Pemerintah Daerah (LKPD) (Studi Pada BPK RI Perwakilan DIY) - Rahmat Gangsar Rizky Rahmat (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to analyze the effect of independence, professionalism, and time budget pressure on the quality of audits of local government financial reports (LKPD) at the Indonesian Supreme Audit Agency (BPK) DIY Representative. This research is included in the quantitative research. The statistical method used to find the hypothesis is multiple linear regression analysis. Collecting data in this study by distributing research questionnaires to auditors who work at the BPK RI DIY Representative by using the total sampling formula. Later on, the results from hypothesis testing show that independence has no significant effect on the quality of LKPD examination, the independent variable of professionalism shows a significant positive effect on the quality of LKPD examination, and the dependent variable has no significant effect on the quality of LKPD examination.